The Most Beautiful Painting in the World: the process as a narrative in Tàpies - Echarri, Fernando; Ortiz-Echagüe, Javier (Arte, Individuo y Sociedad, 2019)
The work of the artist Antoni Tàpies (1923-2012) has been widely studied from different disciplines, including his analytical and syncretic vision. This article tries to analyze one of its aesthetic keys: in particular, the conceptualization of its idea process, using the synthesis that appears in the graphic story "The most beautiful painting in the world" published by Ralph Herrmanns in 1970, in which Tàpies is represented as a character-artist. The study of this graphic story also allows us to advance in the study of some educational variables that can intervene in the teaching-learning processes of the arts, such as the artist's relationship with the educational intention that appears as a moral in the story-tale. In this moral of a fable, as a conclusion or educational synthesis, Tàpies tries to express his aesthetic thinking about the creative process, represented in his artistic work.